Gene expression patterns during anhydrobiosis in Hypsibius exemplaris - Nikupaavola, Tiia (2018)
Identifying and understanding the role of genes underlying adaptive phenotypes is a major goal of modern evolutionary ecology. Anhydrobiosis is phenotypic adaptation that allows individuals to withstand the temporary desiccation of their otherwise aquatic environment. It is common across microinvertebrate groups, namely tardigrades. Gene expression analyses provide a window to the molecular mechanisms that enable organisms to survive and recover from these events. Proteins of three major groups have been suggested to have a key role in such adaptations: heat-shock proteins (HSPs), aquaporins (AQPs) and late embryogenic abundant proteins (LEAs). However, previous studies have largely focused on only a small subset of these proteins, and/or only compared effects between the end points of the anhydrobiosis process (i.e. dry vs. active individuals). In my study, I combine for the first time (i) the simultaneous estimate of expression levels in all three key protein groups, and (ii) a comparison across consecutive anhydrobiosis states (active, transitioning and dry), using the tardigrade Hypsibius exemplaris. Moreover, by using digital droplet PCR (ddPCR), a novel approach that is optimized for small sampling units, I could obtain more precise expression measures. The results show different patterns of gene expression in all target genes. The expression level of HSP70-like 1 dropped by 80% in the dry state compared to the transition state, while the transcript copies halved between active and transitional states. HSP70-like 1 transcript numbers stayed similar between active and transitional states. AQP10 expression levels were 3 time more in the active state and 5 times more in the preconditioning state, while the dry state had 3 times more transcript copies compared to the transitional state. LEA1 showed induction during the preconditioning state, while the expression levels in active, transition and dry states stayed similar. The findings from HSP70-like 1 are similar to expression changes in HSP70-3 observed previously in the tardigrade Milnesium tardigradum. This implies that HSP70-like 1 might have a similar role in H. exemplaris. The induction of AQP10 in preconditioning suggests this gene is important for H. exemplaris when entering anhydrobiosis. The induction of LEA1 in the preconditioning state also suggests this gene has a role in entering anhydrobiosis. In conclusion, this study illustrates the importance of studying species-specific mechanisms of tardigrade adaptation to changing limnoterrestrial conditions as well as provides a benchmark for comparative studies and future experimental research.